A new mononuclear Fe(iii) Mannich-base complex with selective histidine binding and catechol oxidase activity. (13th February 2023) - Mandal, Bikramaditya; Haldar, Anwesha; Ganguly, Rakesh; Saha, Rajat; Mandal, Debdas
Abstract : The design of amino acid sensors have significant applications in biomarkers. Abstract : The design of amino acid sensors have significant applications in biomarkers. Herein, we have developed an achiral Fe(iii )-complex [Fe III L(bzac)] (complex 1 ) (H2 L = N, N ′-dimethyl- N, N ′-bi(2-hydroxy-3, 5-dichlorobenzyl)-ethylenediamine (H2 L ) that shows highly selective sensing of histidine over others in an aqueous methanolic solution. The complex has been synthesized by a simple stirring method using H2 L and benzylacetone (bzac) as the ancillary ligand and characterized by single crystal X-ray diffraction analysis along with other spectroscopic studies. Structural study shows that it is a simple mononuclear complex though the single molecule is chiral; however, the overall crystalline lattice is achiral in nature. In the complex, Fe(iii ) shows distorted octahedral geometry, and each discrete complex is connected by supramolecular hydrogen bonding interactions to form achiral 3D supramolecular structure. Both the absorption spectral analyses reveal that the complex has peaks at 484 nm due to ligand-to-metal charge transfer (LMCT) and emission spectra have a peak at 566 nm. In the presence of histidine, there is a red-shift of about 70 nm and peaks arise at about 564 nm, while the emission spectra shows that the peak at 566 nm disappears completely and a new peak at 603 nm appears. In the presence of other amino acids, there is no such distinct change in both the absorption and emission spectra of the complex. It also acts as an effective catalyst toward the oxidation of 3, 5-di- tert -butylcatechol in methanol solvent.